Radhakrishnan and the ways of oneness of East and West - "Organ, Troy Wilson" (Athens, 1989)
Papers of a conference of the Institute for Environmental Studies, Ramapo College of New Jersey, May, 1986. The book provides an interdisciplinary overview and analysis of radon and the environment. No math. Accessible to lay readers. No index. .
Keywords: "Radhakrishnan, S (Sarvepalli) 1888-1975"